The evolution of fibrin-specific targeting strategies - Stefanelli, Victoria L. (J Mater Chem B, 2015)
Fibrin-specific targeting capabilities have been highly sought for over 50 years due to their implications for bio-molecule delivery, diagnostics, and regenerative medicine. Yet only recently has our full knowledge of fibrin's complex polymerization dynamics and biological interactions begun to be fully exploited in pursuit of this goal. This highlight will discuss the range of rapidly changing strategies for specifically targeting fibrin over the precursor fibrinogen and the advantages and disadvantages of these approaches for various applications.